Migrant–Local Hiring Queues in the UK Food Industry. Issue 5 (8th October 2012) - Scott, Sam
ABSTRACT: The paper argues that a clear migrant–local hiring queue has emerged at the bottom of the UK labour market since EU enlargement (in 2004 and 2007). The hiring queue reflects a preference amongst low‐wage employers in the UK food industry for newly arrived A8 and A2 migrants and related prejudice towards would‐be domestic workers. Using interview and survey evidence – from 37 horticultural growers/processors and 268 farmers, respectively – we describe what these hiring queues look like. We then explain their emergence: arguing that migrant–local hiring queues are predominantly the result of the 'added value' that migrants from the EU periphery bring, over the short term, to the low‐wage workplace. Copyright © 2012 John Wiley & Sons, Ltd.